ANALISIS PENGGUNAAN POLA KOMUNIKASI INTERPERSONAL DIADIK DALAM MENINGKATKAN PERCAYA DIRI MURID MI PUI CIKUMAN BANJARSARI - Kusumasari, Nuruliah; Hidayat, Yusuf; Nugraha, Anggi Purwa (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2025)
Self-confidence is very important aspect to create student’s success in both academic and personal fields. The study aims to know to what extent does diadik interpersonal communication applied by the teacher impact to improve the student’s self-confidence in MI PUI Cikuman Banjarsari. The study used qualitative method under a phenomenological approach. This results of the study showed that diadik personal communication was quite good to solve the student’s problem. Meanwhile, the difficulty faced by the student was: the student doesn't live with his/her parents; the student doesn’t have confident when performs the presentation in front of the class. Then, the solution given was: to solve the first problem is the teacher carried out the intents diadik personal communication (face to face) to the student; to solve the second problem was the teacher gave self-confident understanding to the student, then giving them examples how to perform the presentation in front of the class.